A very light lunch: Interoceptive deficits and food aversion at onset in a case of behavioral variant frontotemporal dementia. Issue 1 (2nd November 2018) - Salvato, Gerardo; Mercurio, Matteo; Sberna, Maurizio; Paulesu, Eraldo; Bottini, Gabriella
Abstract: Introduction: Patients affected by the behavioral variant frontotemporal dementia (bvFTD) frequently experience, at a delayed onset, abnormal eating behavior involving increased food intake. Although delusional food‐related symptoms have attracted much attention, the behavioral and neural features of food aversion manifestations in bvFTD remain poorly documented. Methods: We describe the rare case of a patient with bvFTD presenting with lack of interoception for swallowing and digestion, coupled with a dramatic food aversion at onset. We also compared his MRI scan to 84 healthy individuals using a voxel‐based morphometry approach. Results: We found gray matter density reductions involving the postcentral gyrus bilaterally, insulae, and right medial orbitofrontal cortex. Discussion: Our results shed new light on the behavioral and neuroanatomical features of food aversion and interoception deficits in bvFTD, suggesting that besides orbitofrontal cortex, also a distributed system associated with interoception might play a role in such behavioral manifestation.